People's Republic of China : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Prospects for the future remain favorable, provided that policy actions are taken to address the risks and challenges that China faces. The government recognizes the need to contain investment and credit growth, and has tightened the monetary policy in response. Greater exchange rate flexibility will play a role in contributing to an orderly process for resolving global current account imbalances. Center-local fiscal relations need to be reformed, and such reform will help to rebalance the economy and spread the benefits of growth.